PREVALENCE OF PESTE DES PETITS RUMINANTS VIRUS ANTIBODIES IN SMALL RUMINANTSIN SINDH, PAKISTAN - A. R. Nizamani; Z. A. Nizamani; A. P. Umrani; P. Dewani; M. A. Vandiar; J. A. Gandahi; N. M. Soomro (Journal of Animal and Plant Sciences, 2015)
Peste des petits ruminants (PPR) is an acute viral disease of small ruminants which is clinically characterized by occulo-nasal discharges, oral erosive lesions, diarrhea, pneumonia and leucopenia.It leads to high morbidity and moderate mortality rates.The present study was aimed at determining the seroprevalence of PPR in small ruminants of Sindh province by competitive-ELISA. A total of 7096bloodsamples were collected from sheep (1309) and goats (5787) fromeleven districts of the Sindh. The overall seroprevalence was found to be35.23 percent in the small ruminant population.Prevalence was found higher in sheep (37.2%) than in goats (34.78%). Seroprevalence varied in various age groups and was found to be 33.41%, 33.34% and 39.15% in three age groups, i.e.<1 year, 1 to 2 years and > 2 years, respectively.Prevalence rates were higher in females (35.94%) than in males (31.23%). Prevalence of PPRvaried in various agro-ecological zones of the province. It was found highest in Dadu district (69.3%) and lowest in Badin district (15.7%). Southern coastal districts of Badin (15.7%) and Thatta (30.9%) showed lower and eastern districts of Tando Allah Yar (60.3%) along with Tharparkar (50.3%) a higher seroprevalence of PPR. PPR is endemic in Sindh, therefore there is an urgent needfor preventive vaccination disease control.
Keywords: PPR; Sindh; c-ELISA; Seroprevalence; Goat; Sheep